A National Patient Safety Curriculum in Pediatric Emergency Medicine. Issue 8 (August 2019) - Stankovic, Curt; Wolff, Meg; Chang, Todd P; Macias, Charles
Abstract : Background: Patient safety has become an important and required topic in medical education. A needs assessment showed that pediatric emergency medicine program directors were interested in a common pediatric emergency-specific safety curriculum. Objective: The objective of this study was to describe the development and performance of a web-based patient safety curriculum in pediatric emergency medicine. Methods: A web-based curriculum was created by the Committee on Quality Transformation of the Section of Emergency Medicine for the American Academy of Pediatrics. The curriculum consisted of emergency-specific safety topic didactic sessions with a pretest and posttest assessment. Vignette-based scenarios were also included and were discussed locally by the program directors. Results: Fifty-two percent (37/71) of US Pediatric Emergency Medicine fellowship programs enrolled their fellows in the patient safety curriculum. Overall, 183 Pediatric Emergency Medicine fellows participated in the curriculum. Only 22% (40/183) of fellow participants completed the entire curriculum. The curriculum showed significant improved safety knowledge based upon the pretest and posttest results. Sixty-five percent of responders thought more about safety topics after the curriculum was completed, and 85% witnessed a safety event in the past month, whereas only 48% reported them. Conclusions: An online centralized curriculum is an effective platform for teaching content in quality and safety to a national group of physicians. Local oversight by program directors may improve compliance with curriculum completion. Abstract : Supplemental digital content is available in the text.